Keeping Better Company: Corporate Governance Ten Years on - Jonathan P.Charkham (New York Oxford University Press, 2011)
How should companies be organized? To whom should boards of directors be responsible-shareholders, or a wider group of stakeholders? In this fiercely competitive world we cannot judge our own system of corporate governance in isolation; it must bear comparison with the best. The second edition of this acclaimed and well-established book aims to do just that. Since publication of the first edition interest in corporate governance has greatly increased, codes have proliferated, and principles laid down nationally and internationally. In Keeping Good Company, the author describes developments in the system of corporate governance-both the business environment and the particular structures of company organization-in five major industrial countries: Germany, Japan, France, the USA and the UK. This second edition is fully revised, updated and expanded, and includes a new conclusion looking at a number of ongoing issues in corporate governance, and an appendix discussing the role of international organizations.
Keywords: (ASB-2508) Corporate Governance and Regulation